Dermal cells distribution on laser‐structured ormosils1. (28th November 2011) - Sima, L. E.; Buruiana, E. C.; Buruiana, T.; Matei, A.; Epurescu, G.; Zamfirescu, M.; Moldovan, A.; Petrescu, S. M.; Dinescu, M.
Abstract: Several dermal substitutes for skin grafting are now commercially available, although their performance still needs improvement. Most artificial dermises have a lower take rate than autologous grafts and require more time for sufficient vascular ingrowth to overlay the skin graft. Herein we characterize new two‐dimensional scaffolds for tissue‐engineering applications, which were fabricated by two‐photon polymerization (2PP) of ormosils hybrid materials. For the 2PP experiments, a Ti:sapphire laser was used to induce the photopolymerization. In this study we showed that the polymeric structures with controlled architectures produced via 2PP could be used as scaffolds for the in vitro culture and proliferation of human dermal fibroblasts. Fluorescence microscopy revealed that the fibroblasts' orientation was guided by the scaffold geometry, consisting of ormosils lines or grids. This 'dermal equivalent' was investigated for its ability to accommodate epidermal cells. To evaluate this interaction, two experimental approaches were hence used: (a) fibroblast–melanocyte co‐cultures; and (b) fibroblast–keratinocyte organotypic cultures. During their growth on ormosil scaffolds, productive interaction of fibroblasts with both epidermal cell types was found. Moreover, this pseudo‐dermis was shown to support the growth of keratinocytes for up to 8 days after their seeding. Copyright © 2011 John Wiley & Sons, Ltd.